Towards a Transformation Costs Theory - Noga, Adam (Przyczynek do teorii kosztów transformacji, 2009)
Transformation costs may constitute an interesting basic of transformation theory, explaining its contingencies and its course. They also suggest that household, alone or as the main creator of business, must look for the ways to lower the incurred transformation costs on their own. An outline to such peculiar nano-economics of households, which have to stand up against the tsunami of the global crisis, goes beyond to scope of this article. Outside the big theoretical discussions and political struggles, it is resource-fullness of households that painstakingly creates the nano-economics. big theoretical discussions and political struggles, it is resource-fullness of households that painstakingly creates the nano-economics.
Prace Naukowe Uniwersytetu Ekonomicznego we Wrocławiu = Research Papers of Wrocław University of Economics; 2009; Nr 81, s. 71-83
Keywords: transformation theory; transformation cost; nano-economics; households